Diversity of Bird Species in The Border City of Pontianak, Indonesia, and Sarawak, Malaysia - Agil, Muhamad; Riyadi, Ahmad; Abdillah, Annas Nur; Raihan, Raihan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The island of Kalimantan is an island with a very large area. On this island there are three countries namely Brunei Darussalam, Malaysia and Indonesia. Therefore, there are several areas that are border areas between countries, such as North Kalimantan, Indonesia with Sabah Malaysia, and West Kalimantan, Indonesia with Sarawak, Malaysia. Kalimantan Island is known to have high biodiversity, including a variety of bird species, making it very interesting to explore its species diversity. The purpose of this research is to analyze the diversity of bird species and their conservation status found in the border cities of Pontianak, Indonesia, and Sarawak, Malaysia. The method used in this research is the Point Count Method at each predetermined location. All data obtained were analyzed for their diversity index values and the conservation status of each bird species found was determined based on the International Union for Conservation of Nature and Natural Resources (IUCN). The research results indicate that the bird species diversity index in the border city of Pontianak is 1.795, and Sarawak is 1.70. The research results identified a total of 12 bird species from the two border cities. The bird diversity index value in the border area city of Pontianak is 1.795 and Sarawak is 1.70. The value of the diversity index falls into the moderate category. The conservation status of the 12 bird species found is that one species is classified as Vulnerable (VU) and 11 species are classified as Least Concern (LC).